Efficacy and safety of radiotherapy to delay second-line systemic therapy in patients with oligoprogressive hepatocellular carcinoma: study protocol of a multicentre, single-arm, phase II trial - Haohua Wang; Xiang Zhang; Kunli Zhu; Shumei Jiang; Tianxing Liu; Rui Feng; Xue Dou; Lei Xu; Junyi He; Fang Shi; Jinbo Yue (Therapeutic Advances in Medical Oncology)
Background: Hepatocellular carcinoma (HCC) is a highly aggressive cancer with a paucity of efficacious treatment options, particularly in advanced stages following first-line systemic therapy (FLST). Objectives: The objective of this trial is to assess the efficacy and safety of radiotherapy as a treatment option to prolong progression-free survival (PFS) and delay the necessity for second-line systemic therapy (SLST) in patients with oligoprogressive HCC following FLST. Design: Multicentre, single-arm, phase II trial. Methods and analysis: This prospective, multicentre, single-arm phase II clinical trial will enrol 36 patients with oligoprogressive advanced HCC following FLST. A comprehensive clinical imaging evaluation will be conducted to confirm the presence of oligoprogressive disease, categorized as metachronous oligoprogression, repeat oligoprogression or induced oligoprogression. Furthermore, patients must have demonstrated stability of the primary HCC for a minimum of 3 months during FLST. Eligible patients will receive radiotherapy for all oligoprogressive lesions with a biologically effective dose (LQ, α/β = 10) of at least 60 Gy while continuing their current FLST until disease progression necessitates SLST. The primary endpoint is PFS, with secondary endpoints including objective remission rate, overall survival (OS), disease control rate, safety and duration of disease remission. Ethics: The final protocol was approved by the Ethics Committee of the Affiliated Cancer Hospital of Shandong First Medical University. Discussion: Given the greater number of options for FLST in advanced HCC, which have demonstrated improvements in PFS and OS, and the limited number and less effective SLST options, this phase II trial aims to evaluate the use of radiotherapy to extend PFS and delay the application of SLST in patients with oligoprogressive HCC after FLST. This approach may preserve SLST options for more aggressive, widespread metastatic disease in the future. Trial registration: This study is registered on ClinicalTrials.gov identifier: NCT06261047.